Implementation of agile methodology in developing insurance claim payment application at pharmacies - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
Payment claim management in pharmacies is often conducted manually, which is susceptible to errors and less efficient. To address this challenge, a more structured and effective approach is needed. This research adopts the Agile approach in developing an insurance claim payment application in pharmacies. The Agile approach was chosen for its flexibility in adapting to user needs changes and enabling rapid iterations in application development. Implementing the application with the Agile approach resulted in a product that meets most of the specifications and user expectations, with features such as pharmacy system integration, quick claim reporting, timely payment notifications, and strong data security receiving positive feedback from users. However, user acceptance evaluation also identified some areas that require improvement, such as limited password reset features and less flexible notification options. This research makes a significant contribution to the development of insurance claim payment applications in pharmacies using the Agile approach. The results of this research provide insights into the effectiveness of the Agile approach in this context and lay the groundwork for further improvements and enhancements in the development of similar applications in the future